The effects of school infrastructure on curriculum policy implementation : a case of Mankweng Circuit - Pillay, Rosinah Modikoa (My University, 2022)
Post 1994, the democratic government was tasked with correcting the social and educational injustices prompted by the apartheid regime's colonial system. One of the most crucial aspects was the transformation of the educational system, particularly the curriculum content. However, given that the school's infrastructure was out of date with the status quo, this seemed like a daunting task in recent years. In the sense that it facilitates effective teaching and learning, school infrastructure is critical in the implementation of curriculum policies. Nonetheless, despite the government's efforts to improve school infrastructure, many schools continue to lack access to adequate basic school facilities. This study looked into the effects of school infrastructure on curriculum policy implementation. The qualitative research method was used to successfully respond to the study's objectives. Through a purposive sampling strategy, the research study also used a semi-structured interview questionnaire to elicit the respondents' indepth opinions and knowledge. Also, thematic qualitative analysis was used to derive the study's findings and, as a result, make conclusions and recommendations. According to the findings, there is a severe lack of infrastructure in schools, which has an impact on teaching and learning. Furthermore, the findings revealed that curriculum policy implementation is slow as a result of inadequate infrastructure, a lack of stakeholder involvement, and uninformed teachers. It is recommended that the Department of Basic Education establish networks and partnerships with the private sector, the broader community and non-governmental organisations in order to generate funds for school infrastructure development.
Thesis (M. Administration (Public Administration and Management)) -- University of Limpopo, 2022
Keywords: Curriculum; Curriculum policy implementation; School infrastructure; Public schools.; Education -- Curricula; Public schools; School buildings -- Law and legislation